2006
DOI: 10.1128/aac.01636-05
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Tigecycline in Patients with Complicated Intra-Abdominal or Skin and Skin Structure Infections

Abstract: Tigecycline, a first-in-class expanded glycylcycline antimicrobial agent, has demonstrated efficacy in the treatment of complicated skin and skin structure infections (cSSSI) and complicated intra-abdominal (cIAI) infections. A population pharmacokinetic (PK) model for tigecycline was developed for patients with cSSSI or cIAI enrolled in two phase 2 clinical trials, and the influence of selected demographic factors and clinical laboratory measures was investigated. Tigecycline was administered as an intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
59
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 21 publications
(22 reference statements)
12
59
7
Order By: Relevance
“…Mean parameter values and standard deviations from the pharmacokinetic models are shown in Table 2. Serum clearance is modestly lower than that observed in previous analyses (15); this difference may reflect differences in demographics and/or disease state between studies. Clearly there was a high degree of interindividual variability in tissue pharmacokinetics, as evidenced by the high standard deviations.…”
Section: Demographics As Shown Incontrasting
confidence: 45%
“…Mean parameter values and standard deviations from the pharmacokinetic models are shown in Table 2. Serum clearance is modestly lower than that observed in previous analyses (15); this difference may reflect differences in demographics and/or disease state between studies. Clearly there was a high degree of interindividual variability in tissue pharmacokinetics, as evidenced by the high standard deviations.…”
Section: Demographics As Shown Incontrasting
confidence: 45%
“…The pharmacodynamic studies indicated that the validated TGC regimen could achieve a maximum steady-state serum drug concentration of 0.63 Ϯ 0.28 mg/liter (mean Ϯ standard deviation). Thus, the results do not support TGC use for bloodstream infections caused by organisms for which TGC MICs are Ͼ1 mg/liter (16,20,21). In Taiwan, the MIC 50 and MIC 90 of TGC for MRAB were reported to be 2 and 4 mg/ liter, respectively (10).…”
mentioning
confidence: 69%
“…However, this experiment simulated a higher concentration of tigecycline than those used in our model, and that concentration was maintained over the entire course of the experiment. Clearly, this is not the concentration-time profile exhibited by tigecycline administered clinically at a dose of 50 mg every 12 h, even in the ELF (12,39,44). To achieve an fAUC exposure in ELF of 3.1 g-h/ml, our model simulated a steady-state tigecycline peak concentration of 0.57 g/ml, followed rapidly by an exponential decline in the concentration to approximately 0.21 g/ml, which was then maintained for the 12-h dosing interval (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A dosing strategy was developed using mean pharmacokinetic parameters from a previous population pharmacokinetic study of tigecycline to simulate steady-state tigecycline concentrations in epithelial lining fluid (ELF) after 50-mg doses every 12 h, as depicted in Fig. 1A (44). For these calculations, we assumed that the median area under the curve (AUC) for ELF over the dosing interval was 115% of that in serum, as observed in a population pharmacokinetic analysis of ELF data from healthy volunteers (39).…”
mentioning
confidence: 99%